Analysis of Non-Performing Assets in Indian Banking Sector: Effects of Non-performing Assets on the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The best indicator for the health of the banking industry in a country is its level of Non-performing assets (NPAs). NPAs are one of the major concerns for banks in India. It reflects the performance of banks. Reduced NPAs generally gives the impression that banks have strengthened their credit appraisal processes over the years and growth in NPAs involves the necessity of provisions, which bring down the overall profitability of banks. Non-performing Assets are threatening the stability and demolishing bank’s profitability through a loss of interest income, write-off of the principal loan amount itself. RBI issued guidelines in 1993 based on recommendations of the Narasimham Committee that mandated identification and reduction of NPAs be treated as a ‘national priority’ because the level of NPA act as an indicator showing the bankers credit risks and efficiency of allocation of resource.